2020
DOI: 10.1186/s12998-020-00310-z
|View full text |Cite
|
Sign up to set email alerts
|

Dry needling for spine related disorders: a scoping review

Abstract: Introduction/Background: The depth and breadth of research on dry needling (DN) has not been evaluated specifically for symptomatic spine related disorders (SRD) from myofascial trigger points (TrP), disc, nerve and articular structures not due to serious pathologies. Current literature appears to support DN for treatment of TrP. Goals of this review include identifying research published on DN treatment for SRD, sites of treatment and outcomes studied. Methods: A scoping review was conducted following Levac e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…For MPS, there is a limited number of studies that compare one intervention plus another intervention in the experimental design [12,13]. We aimed to find the most effective intervention method in trapezius MPS by applying classic physical therapy and dry needling or Kinesio taping, and we observed that all the 3 therapies were equally effective (p < 0.05 when compared with baseline) by VAS and SF-36 scores.…”
Section: Discussionmentioning
confidence: 96%
“…For MPS, there is a limited number of studies that compare one intervention plus another intervention in the experimental design [12,13]. We aimed to find the most effective intervention method in trapezius MPS by applying classic physical therapy and dry needling or Kinesio taping, and we observed that all the 3 therapies were equally effective (p < 0.05 when compared with baseline) by VAS and SF-36 scores.…”
Section: Discussionmentioning
confidence: 96%
“…It only involves insertion of thin monofilament needles 2 . Dry needling is usually used to treat musculoskeletal problems such as back or neck pain 3,4 . The needle penetrates the skin and stimulates underlying myofascial trigger points, muscles, ligaments, tendons, and subcutaneous fascia for the management of a variety of neuromusculoskeletal problems 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Dry needling is usually used to treat musculoskeletal problems such as back or neck pain 3,4 . The needle penetrates the skin and stimulates underlying myofascial trigger points, muscles, ligaments, tendons, and subcutaneous fascia for the management of a variety of neuromusculoskeletal problems 4 . Some professional organizations state that dry needling is a procedure that involves needles only inserted into the trigger points 1 .…”
Section: Introductionmentioning
confidence: 99%
“…DN improves sensory, motor, and autonomic symptoms caused by TrPs through mechanical, neurophysiological, and chemical mechanisms [12,13]. DN is effective in LBP [14], but the priority of DN over other treatments in LBP is unclear [15].…”
Section: Introductionmentioning
confidence: 99%